2002
DOI: 10.1089/107632702320934092
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Bioactive Matrix by Modifications of Calcium Sulfate

Abstract: The goal of this study was to define the conditions for the fabrication of a bioactive matrix that induces and supports cell proliferation and tissue regeneration. The proposed hypothesis was that a composite graft could be engineered by the absorption of platelet-rich plasma (PRP) onto calcium sulfate (CS). Evaluation of the biological activity of the engineered grafts was based on osteoblast proliferation studies and scanning electron microscopy (SEM) analyses. Graft samples were created in a standard size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…This is an exothermic setting reaction during which 1 g of hemihydrate CS combines with 186 μl of water [19,20]. Similarly, as described in previous studies [16], CS-Platelet was prepared by mixing hemihydrate CS (Capset, Lifecore Biomedical, Inc. USA for the animal bioassays, and Surgiplaster, ClassImplant, s.r.l. Italy for the human clinical cases) with Platelet-Rich Plasma (PRP) in place of water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an exothermic setting reaction during which 1 g of hemihydrate CS combines with 186 μl of water [19,20]. Similarly, as described in previous studies [16], CS-Platelet was prepared by mixing hemihydrate CS (Capset, Lifecore Biomedical, Inc. USA for the animal bioassays, and Surgiplaster, ClassImplant, s.r.l. Italy for the human clinical cases) with Platelet-Rich Plasma (PRP) in place of water.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that within CS-Platelet, CS is able to activate the platelets present in the PRP without the need for an agonist [16], and to carry and release growth factors in a time-dependent manner [17]. Thus, CS-Platelet is a candidate biomaterial for bone regeneration because it is able to sustain over time the nourishment of the bone defects via the combinatorial delivery of calcium and platelets' multiple biological factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in our laboratory utilized alveolar bone cells in primary explant cultures from human trabecular bone chips that were obtained during routine oral surgical procedures (9)(10)(11)(12)(13). In a recent study we demonstrated their capacity to differentiate into a mature osteoblast phenotype, and some of these cells were utilized in the current study (13).…”
mentioning
confidence: 99%
“…This has been documented by several in vivo studies. 27 Recently, Intini et al 28 used CS as a carrier and releasing device for platelet-rich plasma (PRP) and platelet-derived growth factor. Kim et al 29 used CS and PRP in peri-implant defects, showing successful bone formation.…”
Section: Discussionmentioning
confidence: 99%